Analysis on Islamic Women’s Right and Liberation in An Iranian Film: Osama - Annita Annita (Universitas Multimedia Nusantara, 2015)
Osama speaks about a girl who disguised herself as a boy in order to survive in Taliban’s era. Not only has this film talked about survival, this masterpiece also exposed women’s struggle to get education under the oppression of Taliban. This article will analyze how the filmmaker discusses feminism from the point of view of Islamic women in a very delicate way. Keywords: women’s right, Taliban, Osama